Acute kidney injury - Ronco, Claudio; Bellomo, R; Kellum, John A (Karger, 2007)
Acute kidney injury is defined as an abrupt change in serum creatinine and/or urine output, and a majority of patients admitted to the ICU have some evidence of the disorder. Unfortunately, treatment for this complex syndrome is as yet lacking and understanding is limited. An interdisciplinary panel of experts has contributed to this volume, illuminating some of the fundamental and complex aspects of the disorder ranging from pathophysiology to treatment, from emerging biomarkers to genetic polymorphisms. Other contributions focus on immunological issues or the many complications of acute kidney injury and co-morbid conditions encountered, covering the fundamentals as well as the latest developments. Moreover, important technical aspects of extracorporeal therapies including vascular access, anticoagulation or fluid composition are introduced, and different approaches to renal support from intermittent dialysis to continuous therapies and hybrid techniques are discussed. A description of advanced extracorporeal techniques of organ support and their role in the management of sepsis and acute kidney injury in the context of an overall strategy of multi-organ failure management concludes the discussions. This volume not only provides a practical and up-to-date summary of current knowledge and technology, but also imparts a fundamental understanding of the pathogenesis and likely future developments in this field. It also serves to challenge and re-examine the fundamental underlying assumptions we hold regarding critical illness in general and acute kidney injury in particular.
Contributions to nephrology, ISSN 0302-5144 v. 156
Keywords: ledviny; péče o pacienty v kritickém stavu; nefrologie; Acute Kidney Injury; Sepsis; Kidney; Critical Care; Renal Replacement Therapy; sepse; náhrada funkce ledvin; akutní poškození ledvin